Pendampingan dan Pemanfaatan Media Sosial pada UMKM Segar Rasa - Dwi Puspita Anggraeni (Biro Pengelolaan Penelitian dan Pengabdian Kepada Masyarat SETIA Ngabang, 2025)
This community service activity (PKM) aims to improve operational efficiency and service quality at Santosa Catering through the implementation of a web-based catering ordering system. Santosa Catering, as a micro business, faces obstacles in managing orders that are still done manually, which causes inaccurate stock information, delays in delivery, and limited customer access to menus and prices. Through a Diffusion of Science and Technology and Knowledge Transfer approach, a web-based ordering system was developed and implemented to support business operations. The system allows customers to access real-time menu information, place online orders, and choose preferred payment methods, while the owner and staff were given intensive training to effectively operate the system. The evaluation results showed significant improvements in all aspects of assessment, including understanding of system features, operational skills, time efficiency, and customer satisfaction, as shown in the comparison chart of pretest and posttest results. The system not only optimizes operational processes but also increases customer satisfaction, strengthens business competitiveness, and has the potential to become a model for other micro businesses in utilizing digital technology. Thus, this PKM activity is expected to contribute to the sustainability of Santosa Catering's business in the digital era.